Pemanfaatan Batu Sungai Masuppu Kecamatan Masanda Dalam Campuran AC-WC - Febrianto; Alpius; Sufiati Bestari (Paulus Civil Engineering Journal, 2021)
Highway is part of the Science of Civil Engineering and always develops over time. In increasing the provision of land transportation, roads are important infrastructure that must be considered in development. The availability of adequate road infrastructure will have a positive impact on the development of community activities from the economic, political, social, cultural, defense and security aspects of the country.This research was intended to utilize Masuppu River Stones in Masanda Subdistrict as a mixture of AC-WC. The methodoIogy in this research is to conduct a series of tests for the characteristics of coarse, fine, and fiIIer aggregates, then design the composition of the Laston AC-WC mixture and the Marshall test to obtain the characteristics of the mixture and the MarshaII immersion test to obtain the immersion index (IP) / residuaI strength index (IKS) / durabiIity of the mixture with optimum asphaIt content. The results of research carried out at the Laboratory of Engineering and AspaI Functions of Engineering Department of Civil Engineering, Christian University of Indonesia, PauIus Makassar, show that the characteristics of the pavement material in the form of Masuppu River rock, Masanda District, meet the specifications as a road pavement coating material.